2021
DOI: 10.1371/journal.pone.0257971
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pathogenic Leptospira species and serovars in New Zealand using metabarcoding

Abstract: Leptospirosis is a zoonotic disease of global importance. The breadth of Leptospira diversity associated with both human and animal disease poses major logistical challenges to the use of classical diagnostic techniques, and increasingly molecular diagnostic tools are used for their detection. In New Zealand, this has resulted in an increase in positive cases reported nationally that have not been attributed to the infecting serovar or genomospecies. In this study, we used data from all pathogenic Leptospira g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Such information provides a vital contribution to the planning and implementation of effective prevention strategies [ 4 , 23 , 24 ]. As 16S rRNA gene sequencing has poor discriminatory strength and whole genome sequencing is currently impractical for routine strain typing, additional gene targets, such as secY and glmU genes, have been utilized to type Leptospira species [ 6 , 11 , 25 , 26 ]. LipL32 gene PCR sequencing has also been used extensively because it is a robust target for leptospirosis diagnosis and only detects pathogenic leptospires [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such information provides a vital contribution to the planning and implementation of effective prevention strategies [ 4 , 23 , 24 ]. As 16S rRNA gene sequencing has poor discriminatory strength and whole genome sequencing is currently impractical for routine strain typing, additional gene targets, such as secY and glmU genes, have been utilized to type Leptospira species [ 6 , 11 , 25 , 26 ]. LipL32 gene PCR sequencing has also been used extensively because it is a robust target for leptospirosis diagnosis and only detects pathogenic leptospires [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that whole genome sequencing is still not practical for routine strain typing and 16S ribosomal RNA (rRNA) gene sequencing provides limited discriminatory power, sequence information from other gene targets, such as the ppk, secY, flaB, lfb1, and glmU genes, have been used to type Leptospira species, 15,[18][19][20] as well as for PCR-based diagnostic testing. 21 The use of lipL32 gene PCR sequencing has been particularly widespread, because lipL32 gene PCR is a sensitive target for diagnosis of leptospirosis and only detects pathogenic leptospires.…”
Section: Current Approaches To Leptospiral Strain Typingmentioning
confidence: 99%
“…20 A simplified 3-locus (adk, lipL41, mreA) scheme for direct application to clinical specimens was recently described, 26 although this still requires gel electrophoresis followed by sequencing, which is not practical in a routine clinical laboratory setting. After examination of 598 Leptospira published genomes from 20 P1 species, investigators 19 in New Zealand identified the glmU locus as having sufficient discriminatory power to differentiate among serovars circulating in New Zealand. Direct application of glmU PCR sequencing to the urine of infected cattle 25 was used to deduce infecting serovars.…”
Section: Current Approaches To Leptospiral Strain Typingmentioning
confidence: 99%
See 2 more Smart Citations